Reduced perfusion in Broca's area in developmental stuttering. Issue 4 (30th December 2016) - Desai, Jay; Huo, Yuankai; Wang, Zhishun; Bansal, Ravi; Williams, Steven C. R.; Lythgoe, David; Zelaya, Fernando O.; Peterson, Bradley S.
Abstract: Objective: To study resting cerebral blood flow in children and adults with developmental stuttering. Methods: We acquired pulsed arterial spin labeling magnetic resonance imaging data in 26 participants with stuttering and 36 healthy, fluent controls. While covarying for age, sex, and IQ, we compared perfusion values voxel‐wise across diagnostic groups and assessed correlations of perfusion with stuttering severity within the stuttering group and with measures of motor speed in both groups. Results: We detected lower regional Cerebral Blood Flow (rCBF) at rest in the stuttering group compared with healthy controls in Broca's area bilaterally and the superior frontal gyrus. rCBF values in Broca's area bilaterally correlated inversely with the severity of stuttering and extended posteriorly into other portions of the language loop. We also found increased rCBF in cerebellar nuclei and parietal cortex in the stuttering group compared with healthy controls. Findings were unchanged in child‐only analyses and when excluding participants with comorbid illnesses or those taking medication. Conclusions: rCBF is reduced in Broca's region in persons who stutter. More severe stuttering is associated with even greater reductions in rCBF to Broca's region, additive to the underlying putative trait reduction in rCBF relative to control values. Moreover, a greater abnormality in rCBF in the posterior language loop is associated with more severe symptoms, suggesting that a common pathophysiology throughout the language loop likely contributes to stuttering severity. Hum Brain Mapp 38:1865–1874, 2017 . ©2017 Wiley Periodicals, Inc.